Field Screening of Seven Cultivars of Cabbage Against Cabbage Butterfly (Pieris brassicae) and Cabbage Aphids (Brevicoryne brassicae) at Gkuleshor, Baitadi, Nepal - Singh, Narendra Bahadur; Dhungana, Santosh; Adhikari, Srijana; Chapagain, Dipesh; Ghimire, Nawaraj; DC, Sarad (Nepalese Horticulture, 2020)
Field screening of seven cultivars of cabbage namely: Green Crown, Green Top, Green Coronet, Pioneer, Nepa Round, Copenhagen Market and Golden Acre were carried out against cabbage butterfly (Pieris brassicae) and cabbage aphid (Brevicoryne brassicae) at the research farm of entomology section, Gokuleshwor Agriculture and Animal Science College, Baitadi in RCBD design from October 2017 to February 2018. Five plants were tagged randomly after transplanting in field excluding border plants in each plot. Data were collected for the population dynamics of cabbage butterfly larvae and cabbage aphid on weekly basis. None of the seven cultivars were found resistant to cabbage butterfly and cabbage aphid, however their population density varied on tested cultivars. Cabbage butterfly population was recorded the highest on the cultivar Pioneer (22.88 larvae/plant) and the lowest on the cultivar Copenhagen Market (10.06 larvae/plant), and other cultivars were of intermediate types. Similarly, the population density of aphid ranged from 36.70 to 105.58 aphids/leaf. The highest population density of aphid was recorded on cultivar Green Crown (105.58 aphids/leaf) and the lowest on cultivar Copenhagen Market (39.82 aphids/leaf. From the results, Copenhagen Market proved to be the best against both cabbage butterfly and cabbage aphids.